Analisis Pelatihan Dan Pengembangan Sumber Daya Manusia Pada Kinerja Karyawan Di Desa Cintakarya Kecamatan Sindangkerta - Nurdin, Nurdin Latif; Dewi, Lies Anggi Puspita (Peneliti.net, 2025)
This research aims to analyze training and human resource development on employee performance in Cintakarya Village, Sindangkerta District. In the era of globalization and rapid technological development, training and development have become key elements in managing human resources effectively. This research uses a qualitative approach with a case study method. Data was collected through in-depth interviews and documentation from employees in Cintakarya Village. The research results show that the training and development program implemented has had a positive impact on increasing employee skills, productivity and work efficiency. However, there are several obstacles that reduce the effectiveness of training, such as limited facilities and less than optimal management support. This research provides recommendations for improving the quality of training and development in the future to achieve more optimal employee performancea.